Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1159/000526367
|View full text |Cite
|
Sign up to set email alerts
|

Elevated CXCL14 in Induced Sputum Was Associated with Eosinophilic Inflammation and Airway Obstruction in Patients with Asthma

Abstract: <b><i>Introduction:</i></b> CXCL14 involved in inflammatory processes was upregulated in the asthma expression profile datasets in our pilot study. However, the expression of CXCL14 in induced sputum and its potential clinical role in asthma were poorly reported. <b><i>Objective:</i></b> We sought to detect CXCL14 expression in airway epithelium and induced sputum cells of asthma and explore its potential clinical implications. <b><i>Methods:</i>… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…In this study, we have identified four hub genes that are associated with asthma. Previous research has demonstrated that two of these genes, namely POSTN and SERPINB2, are considered T2 signature genes and have shown promise as potential biomarkers (Burgess et al 2021 ; Du et al 2022 ; Mo et al 2019 ). However, the functional roles of CCDC167 and SEC14L1 in the context of asthma have yet to be fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we have identified four hub genes that are associated with asthma. Previous research has demonstrated that two of these genes, namely POSTN and SERPINB2, are considered T2 signature genes and have shown promise as potential biomarkers (Burgess et al 2021 ; Du et al 2022 ; Mo et al 2019 ). However, the functional roles of CCDC167 and SEC14L1 in the context of asthma have yet to be fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Noticeably, the aforementioned signaling pathways are associated with inflammation and can promote the secretion and release of inflammatory mediators, which have a critical effect in the asthma pathogenesis. Abnormally high levels of inflammatory factors have been observed in the pathogenesis of asthma [ 40 ]. As important proinflammatory cytokines, IL-4 and IL-17, mediate the aggregation of eosinophils in the respiratory tract [ 41 ] and they also activate and stimulate the generation of immunoglobulin (Ig)E, which binds to mast cells and basophil surface receptors, triggering inflammation [ 42 ].…”
Section: Discussionmentioning
confidence: 99%